1990
DOI: 10.1159/000267022
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Measurement of Nuclear RNA Content in Uveal Melanoma

Abstract: We retrospectively studied the nuclear RNA content in uveal melanomas with known, long-term follow-up. Thirty patients had spindle cell melanomas, 25 had mixed cell tumors, and 9 had epithelioid cell neoplasms. Epithelioid cell types had a higher nuclear RNA content compared to mixed or spindle cell types (p < 0.05). Using the Cox proportional hazards model, the nuclear RNA content appeared to be an independent prognostic indicator in uveal melanomas, and an increased nuclear RNA content was associated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Flow cytometry and image analysis have been used to predict survival in both dermatological and uveal malignant melanomas with mixed results. In the ophthalmic literature, Char and associates9 15 have reported that both DNA and RNA ploidy correlate with duration of survival but Shapiro16 or McLean" could find no such association. Fuchs17 attempted to study the correlation between pathological type and ploidy and could find no relation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Flow cytometry and image analysis have been used to predict survival in both dermatological and uveal malignant melanomas with mixed results. In the ophthalmic literature, Char and associates9 15 have reported that both DNA and RNA ploidy correlate with duration of survival but Shapiro16 or McLean" could find no such association. Fuchs17 attempted to study the correlation between pathological type and ploidy and could find no relation.…”
Section: Discussionmentioning
confidence: 97%
“…The relative odds of having mixed pathology given that the tumour was aneuploid as against diploid was 1-17 with a 95% confidence interval between 0 47 and 1-87. significant. Specifically, the relative risk of death for each unit increase in SPF is [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] (variable estimate 0-165, SE=0-0741, p=0026). Stated another way, for every unit increase in SPF the risk of death increased by 17%.…”
Section: Dna Index and Pathological Typementioning
confidence: 99%